UPAYA PETANI KELAPA SAWIT DALAM MENINGKATKAN PRODUKSI TANAMAN KELAPA SAWIT DI NAGARI PUNGGASAN TIMUR KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Fitri, Nurma - (STKIP PGRI Sumbar, 2014)
This study aims to obtain, process, analyze and discuss data on: land preparation, seeding, planting, fertilizing, pest eradication in Nagari Punggasan Timur Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan.The research method is classified as descriptive research. The study population was all palm oil growers in Nagari Punggasan Timur Kecamatan Linggo Sari Baganti Kabipaten Pesisir Selatan. Sampling technique in this study were taken by random sampling of 10% of family households existing oil palm farmers in the Eastern District of Nagari Punggasan timur Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan. The number of respondents in this study were 50 families. Data collection techniques used were interviews and observation, data collection tools by using a questionnaire study.The results showed that: 1). Efforts of farmers in cultivation of oil palm plantations in Nagari Punggasan Timur Kecamatan Linggo Sari Baganti Kabupaten Pesisir Selatan, a. land area of oil palm plantations managed Â± 2 Ha, b. Place oil palm planting in the field. 2). Efforts of farmers in oil palm nursery in Nagari East Punggasan Linggo Sari subdistrict Baganti South Coastal District, a. Nursery container or use a poly bag, b. Acquisition of early seedling nursery place purchased. 3). Efforts of farmers in the planting of oil palm plantations in East Punggasan Nagari Linggo Sari subdistrict Baganti South Coastal District, a. Right season for planting at the beginning of the rainy season, b. Month is right for planting in October or November. 4). Efforts of farmers in oil palm crop fertilization in Nagari East Punggasan Linggo Sari subdistrict Baganti South Coastal District, a. Type of fertilizer used for crops of palm oil N, P, K plus urea, b. Fertilization on plant palm oil 2x a year. 5). Efforts of farmers in pest control palm plants in Nagari East Punggasan Linggo Sari subdistrict Baganti South Coastal District, a. The plant parts are often damaged palm found in the bunches, b. Diseases in plants palm disease caused by a virus.